Knowledge and awareness of oral cancer: A cross-sectional survey in Trieste, Italy - Rupel, Katia; Biasotto, Matteo; Gobbo, Margherita; Poropat, Augusto; Bogdan Preda, Magdalena Theodora; Borruso, Giuseppe; Torelli, Lucio; Di Lenarda, Roberto; Ottaviani, Giulia (Frontiers in Oral Health, 2023)
The aim of the study was to verify the knowledge on oral cancer and to assess possible differences in awareness and information basing on different demographic and subject-related factors. An anonymous survey was provided to 750 random subjects using online-based questionnaires. Statistical analysis was performed in order to evaluate the influence of demographic variables (gender, age, education) on knowledge of oral cancer and its risk factors. 68.4% of individuals knew about the existence of oral cancer, mostly from media and family/friends. Awareness was significantly influenced by gender and higher education, but not by age. Most participants recognized smoking as a risk factor, but alcohol abuse and sunlight exposure are less known, especially among less educated subjects. On the contrary, our study shows a diffusion of false information: more than 30% of the participants indicated the possible role of amalgam fillings in oral cancer onset, independently of gender, age or education. The results of our study suggest the need for oral cancer awareness campaigns, where school and healthcare professionals should be actively involved in promoting, organizing and finding methods to monitor the medium and long-term efficacy with proper methodological quality.